Gambaran Disonansi Kognitif pada Wanita Perokok Dewasa Muda Berpendidikan Tinggi - Fitri, Rani Agias (Bina Nusantara University, 2013)
This research aims to get the description of cognitive dissonance of high educated young adult smoker women, such as the source of dissonance and how to lessen their dissonance. By qualitative research method through depth interview with four research subjects, it is found out that logical inconsistency, general opinion, and past experience are the source of dissonance. Culture norm becomes the source of dissonance only on three subjects. The way the four subjects lessen their cognitive dissonance are changing behavior element and increasing cognitive element whereas changing cognitive element is only done by one subject.